Stability analysis for seed yield and yield attributing traits in fennel (Foeniculum vulguare mill.) - Singh, S Sahu, S L Sawargaonkar, A K (Journal of Spices and Aromatic Crops, 2018)
Study was carried to evaluate phenotypic stability of 13 genotypes of fennel for seed yield and yield attributing traits. Out of 13 genotypes, three were checks (RF 205, RF 201 and local fennel) grown in Randomized Block Design (RBD) with three replications in each year. The significant genotypic differences were observed for all the characters suggesting differential responses of genotypes to the environmental changes. The results showed that among 13 genotypes RF 205 and Local fennel were found stable for seed yield/ plant, FNL 69 for days to flower, FNL 70 and RF 101 for primary branches/ plant, FNL 74 for umbels/ umbellet and FNL 71 for umbels/ plant. The results revealed that some reliable predictions about G x E interaction as well as its unpredictable components contributed significantly in determining the stability of genotypes. The wider stability recorded by RF 205, RF 201 and local fennel during all the three years which will be useful for development of high yielding varieties of fennel.